The Historiography of Genocide - Weiss-Wendt, Anton. author. aut Link
XV, 640 p.
Keywords: The Historiography of Genocide is an indispensable guide to the development of the emerging discipline of genocide studies and the only available assessment of the historical literature pertaining to genocides.